Transformation of Education at State Elementary School 1 Nunggalrejo through the "SIKOP" Program (Santun, Inovatif, Kolaboratif, Obyektif, and Profesional) - Herawati Eka Wahyuni; Irwandani (SAKAGURU: Journal of Pedagogy and Creative Teacher, 2024)
The curriculum development at State Elementary School 1 Nunggalrejo is not yet aligned with the school's needs, vision, mission, and goals. The performance of educators and educational staff remains low, with teaching done merely as a formality. Learning is teacher-centered, monotonous, static, and unengaging, and there is no significant improvement in student character formation. Additionally, there is a lack of supportive environments for information on nutrition health and food safety. The objective of this community service activity is to enhance the quality of education at State Elementary School 1 Nunggalrejo by developing a curriculum based on the school's needs, implementing effective and meaningful learning, and creating a safe and comfortable environment with positive discipline. Additionally, this activity aims to significantly transform student character and provide a supportive environment for nutrition health information and food safety through PJAS. This research method uses a descriptive qualitative approach with data source triangulation, including interviews with parents and teachers, direct observation, and analysis of document. The impact and results of this initiative include improved professional competence of the school principal and teachers, enhanced character education aligning with the Pancasila Student Profile, more meaningful and effective student-centered learning, students achieving both academic and non-academic success, optimized learning communities, and the creation of a healthy, safe, comfortable, and enjoyable learning environment based on positive discipline. The implementation of the SIKOP Program at State Elementary School 1 Nunggalrejo has successfully demonstrated its effectiveness in improving the quality of school education and has significantly contributed to shaping students' character and enhancing overall school conditions.